2022
DOI: 10.3171/case21533
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive endoscopic approach to perform complete coccygectomy in patients with chronic refractory coccydynia: illustrative case

Abstract: BACKGROUND Coccydynia refers to debilitating pain in the coccygeal region of the spine. Treatment strategies range from conservative measures (e.g., ergonomic adaptations, physical therapy, nerve block injections) to partial or complete removal of the coccyx (coccygectomy). Because the surgical intervention is situated in a high-pressure location close to the anus, a possible complication is the formation of sacral pressure ulcers and infection at the incision site. OBSERVATIONS In this case report, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(27 reference statements)
0
2
0
1
Order By: Relevance
“…This procedure has been termed "coccygeoplasty," and the utility has gained recent popularity. Another approach involves the use of endoscopy to circumvent the morbidities inherent to the traditional open coccygectomy 55 . The following therapeutic algorithm has been proposed by Fogel et al 4 .…”
Section: Gonnade Et Al Described Their Techniquementioning
confidence: 99%
“…This procedure has been termed "coccygeoplasty," and the utility has gained recent popularity. Another approach involves the use of endoscopy to circumvent the morbidities inherent to the traditional open coccygectomy 55 . The following therapeutic algorithm has been proposed by Fogel et al 4 .…”
Section: Gonnade Et Al Described Their Techniquementioning
confidence: 99%
“…Загальними показаннями до кокцигектомії є нестабільність куприка, підвивих і куприкова спікула (остеофіт) [34]. У нашій серії ін'єкційного лікування НВ було дос татньо, щоб забезпечити тривале полегшення болю в усіх пацієнтів.…”
Section: таблиця 2 динаміка оцінки за ваш і шк (N=48)unclassified
“…[31,32] The description of the disease was given back in the 1960s by Thiele, and it is still considered accurate and true. Patients describe the pain as sharp, stabbing or aching pain in the coccygeal segments [8,33] Pain can be mild but severe cases are reported with agonizing pain that affects the daily functioning of individuals. [34] Previous studies have shown that pain is experienced particularly when sitting on hard surfaces.…”
Section: Literature Reviewmentioning
confidence: 99%